Beginning JavaServer pages - Chopra, Vivek (Wrox beginning guides., 2005)
JSP is one of the core technologies for server-side Java applications and the 2.0 release, which this book covers in detail, makes JSP an even more powerful tool Walks Java programmers and Web developers through JSP fundamentals, including JSP syntax and directives, JSP Expression Language, JSP Tag libraries, JSTL, and techniques for testing and debugging Shows how to use JSP in real-world Web applications along with open source frameworks such as Struts, WebWork, and Turbine, software design methodologies, and developer tools like Ant, jUnit, and CVS, as well as popular IDEs (integrated development environmnents) Each chapter has an exercise section with solutions on the companion Web site.